Rapid Visual Detection of Methicillin-Resistant Staphylococcus aureus in Human Clinical Samples via Closed LAMP Assay Targeting mecA and spa Genes - Noora S. A. Abusheraida; Asraa A. H. AlBaker; Asmaa S. A. Aljabri; Hana A. Abdelrahman; Hassan Al-Mana; Godwin J. Wilson; Khalid A. Anan; Nahla O. Eltai (Microorganisms, 2024)
The emergence of antimicrobial resistance (AMR), particularly methicillin-resistant Staphylococcus aureus (MRSA), poses a significant global health threat as these bacteria increasingly become resistant to the most available therapeutic options. Thus, developing an efficient approach to rapidly screen MRSA directly from clinical specimens has become vital. In this study, we establish a closed-tube loop-mediated isothermal amplification (LAMP) method incorporating hydroxy-naphthol blue (HNB) colorimetric dye assay to directly detect MRSA from clinical samples based on the presence of mecA and spa genes. In total, 125 preidentified S. aureus isolates and 93 clinical samples containing S. aureus were sourced from the microbiology laboratory at Hamad General Hospital (HGH). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were computed based on conventional PCR. The assay demonstrated 100% specificity, 91.23% sensitivity, 0.90 Cohen Kappa (CK), 100% PPV, and 87.8% NPV for the clinical samples, while clinical isolates exhibited 100% specificity, 97% sensitivity, 0.926 CK, 100% PPV, and 88.89% NPV. Compared to cefoxitin disk diffusion, LAMP provided 100% specificity and sensitivity, 1.00 CK, and 100% for PPV and NPV. The study revealed that the closed-tube LAMP incorporating (HNB) dye is a rapid technique with a turnaround time of less than 1 h and high specificity and sensitivity.